2018
DOI: 10.3389/fphar.2018.00897
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Responses to Psychedelics: A Prospective Study

Abstract: Responses to psychedelics are notoriously difficult to predict, yet significant work is currently underway to assess their therapeutic potential and the level of interest in psychedelics among the general public appears to be increasing. We aimed to collect prospective data in order to improve our ability to predict acute- and longer-term responses to psychedelics. Individuals who planned to take a psychedelic through their own initiative participated in an online survey (www.psychedelicsurvey.com). Traits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
387
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 288 publications
(426 citation statements)
references
References 77 publications
(123 reference statements)
34
387
2
3
Order By: Relevance
“…Recent clinical trials have demonstrated potent and enduring antidepressive and anxiolytic effects of classical psychedelic drugs psilocybin and LSD Carhart-Harris et al 2016;Horstmann et al 2010;Ross et al 2016;Griffiths et al 2016;Grob et al 2011). Several studies have highlighted the mystical nature of the subjective experience resulting from administration of high dose psilocybin or LSD as a mediator for the psychiatric therapeutic benefits (Russ et al 2019;Garcia-Romeu et al 2014;Roseman et al 2018;Haijen et al 2018). However, recent evidence of sustained antidepressant-like effects of psilocybin in an animal rodent model for the study of depression after only a single dose suggests that solely biological mechanisms dependent on 5-HT 2A receptor activation may effectively underlie key CNS effects observed for this class of drug (Hibicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials have demonstrated potent and enduring antidepressive and anxiolytic effects of classical psychedelic drugs psilocybin and LSD Carhart-Harris et al 2016;Horstmann et al 2010;Ross et al 2016;Griffiths et al 2016;Grob et al 2011). Several studies have highlighted the mystical nature of the subjective experience resulting from administration of high dose psilocybin or LSD as a mediator for the psychiatric therapeutic benefits (Russ et al 2019;Garcia-Romeu et al 2014;Roseman et al 2018;Haijen et al 2018). However, recent evidence of sustained antidepressant-like effects of psilocybin in an animal rodent model for the study of depression after only a single dose suggests that solely biological mechanisms dependent on 5-HT 2A receptor activation may effectively underlie key CNS effects observed for this class of drug (Hibicke et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although psilocybin dose is the most important determinant of the acute psychedelic experience, there is considerable inter-and intra-individual variability in subjective responses to psilocybin [55][56][57][58]. To what extend responses to psilocybin varied among studies included in our main analysis is reflected in heterogeneity parameters.…”
Section: Variability Of Subjective Experiencesmentioning
confidence: 99%
“…In general, current mood and psychological distress prior to the psilocybin administration have been shown to contribute to the subjective experience [55,62,63]. Previous work demonstrated that the trait absorption and having clear intentions strongly correlated with all subjective experience measures [55,56]. Further, scoring high on trait extroversion was associated with increases in visionary experience [55,63,64].…”
Section: Variability Of Subjective Experiencesmentioning
confidence: 99%
See 2 more Smart Citations